2018
DOI: 10.1002/clc.22857
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term impacts of hemodialysis on the right ventricle: Assessment via 3‐dimensional speckle‐tracking echocardiography

Abstract: Background Right ventricular (RV) dysfunction is a major cause of death in patients undergoing maintenance hemodialysis (MHD). We used 3‐dimensional speckle‐tracking echocardiography (3DSTE) to evaluate long‐term impacts of MHD on RV function. Hypothesis In this study, RV dysfunction in MHD patients will be revealed and studied in depth by 3DSTE. Methods Echocardiography was performed on 110 consecutively enrolled individuals: 30 controls and 80 patients with MHD. Conventional echocardiographic parameters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…Our findings of the association between diastolic dysfunction and IDH were similar to those of another study [ 16 ]. The mechanisms involving IDH are multifactorial, including inadequate intravascular volume refilling, autonomic dysfunction, abnormal vascular compliance and poor cardiac performance such as LV systolic and diastolic dysfunction and acute hypovolemia during ultrafiltration dialysis [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings of the association between diastolic dysfunction and IDH were similar to those of another study [ 16 ]. The mechanisms involving IDH are multifactorial, including inadequate intravascular volume refilling, autonomic dysfunction, abnormal vascular compliance and poor cardiac performance such as LV systolic and diastolic dysfunction and acute hypovolemia during ultrafiltration dialysis [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings have also revealed that patients with IDH had greater increases in EF and greater decreases in mLVESV during HD. Previous studies have indicated a decline of EF at mid-HD as a possible predictor of IDH using real-time 3D echocardiography [ 8 , 16 ]. However, consecutive assessments of echocardiographic changes at three different time points of a single HD session enabled a more in-depth assessment of dynamic heart performances in IDH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hemodialysis involves large and frequent fluid shifts. RV dysfunction has been associated with intradialytic hypotension, which results in myocardial stunning and ischemia [23]. While we found that duration of dialysis was not significantly associated with development of RV dysfunction or RV dilation, this may be a consequence of evaluating a small study population.…”
Section: Discussioncontrasting
confidence: 68%
“…Hence, 3D-STE displays the potential to identify patients with HFpEF at high risk of poor clinical outcomes [ 95 ]. In addition, the main causes of death in maintenance hemodialysis patients are cardiovascular disease, and RV dysfunction is associated with increased cardiovascular morbidity and mortality [ 96 ]. Sun et al investigated the RV function in 80 patients with maintenance hemodialysis and 30 healthy subjects using 3D-STE.…”
Section: Three-dimensional Speckle-tracking Echocardiography In Hf Pa...mentioning
confidence: 99%